Calculati -13+(-2-3)
(-4+7)-(-2-3)+(-6+1)
Răspunsuri la întrebare
Răspuns de
5
- 13 + ( - 2 - 3 ) =
= - 13 + ( - 5 ) =
= - 13 - 5 =
= - 18
( - 4 + 7 ) - ( - 2 - 3 ) + ( - 6 + 1 ) =
= 3 - ( - 5 ) + ( - 5 ) =
= 3 + 5 - 5 =
= 8 - 5 =
= 3
= - 13 + ( - 5 ) =
= - 13 - 5 =
= - 18
( - 4 + 7 ) - ( - 2 - 3 ) + ( - 6 + 1 ) =
= 3 - ( - 5 ) + ( - 5 ) =
= 3 + 5 - 5 =
= 8 - 5 =
= 3
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Fizică,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă